Generalized Einstein-Power Maxwell theory in 2+1-dimensions - Amirabi, Z. (Springer Heidelberg, 2021)
Using the generalized Einstein-Power Maxwell Lagrangian which has been proposed very recently by Mazharimousavi (Class Quantum Gravity 37:197001, 2020), we find an electric black hole solution in 2+1-dimensions. The solution is singular and non-asymptotically flat associated with only one horizon. The thermodynamic properties are investigated, and it is shown that the black hole is thermally stable. In the context of the extended thermodynamic phase space, we find Smarr's formula consistent with the first law of the black holes.
Keywords: Rotating Black Branes; Holes; Thermodynamics; Supergravity; Energy